Wearable bio-inspired pulsating flow cooling for live garments - Luk, Patrick Chi-Kwong; Tang, Jiawei (IEEE, 2022)
In human experience, it has been well known that temperature induced aggravations, such as heatstroke, heat cramps, dehydration, and frostbite, are among the most common health hazards. For those who live or work in prolonged and extreme temperature conditions, the aggravation may lead to fatal consequences. Temperature control systems such as air conditioning and central heating have been investigated and implemented to provide people a comfortable, and more importantly, livable temperature. However, these systems could be cumbersome to implement in an outdoor or confined environment. Moreover, they lack flexibility such mobility and adaptable temperature for individual needs. In this study, a wearable bio-inspired pulsating (discontinuous) flow cooling system with superior heat exchange efficiency to conventional steady (continuous) flow system, is proposed. Based on a novel array of the cooling tubes, an empirical approach is adopted to avoid complex numerical analysis of the thermal fluid dynamic involved. The prototypes of the two cooling flow systems are built and their performances compared. The results show that the proposed system not only demonstrates better cooling, but also offers potential flexibility that allows personalized temperature conditioning in a ‘live’ garment.
Keywords: bio-inspired systems; pulsating cooling; personalized cooling; wearable temperature conditioning; live garment; empirical approach